33.3k views
1 vote
Hey can you please help me posted picture of question :)

Hey can you please help me posted picture of question :)-example-1

1 Answer

6 votes
Answer:
The roots are:
( √(3) + 3 )/(2) and
(- √(3) + 3 )/(2)

Step-by-step explanation:
First, we would need to put the equation is standard form which is as follows:
ax² + bx + c = 0
This can be done as follows:
4x² - 12x + 9 - 3 = 0
4x² - 12x + 6 = 0

By comparison, we would find that:
a = 4
b = -12
c = 6

To get the roots, we would substitute in the quadratic formula shown in the attached image.

Doing this, we would find that:
either x =
( √(3) + 3 )/(2)

or x =
(- √(3) + 3 )/(2)

Hope this helps :)
Hey can you please help me posted picture of question :)-example-1
User Leiko
by
6.2k points